Kapabilitas Ekonomi Sirkular dalam Sektor UMKM Kota Surakarta Menuju Smart-Sustainable City - Muhammad Alfarizi; Ngatindriatun Ngatindriatun (Jurnal Bengawan Solo Pusat Kajian Penelitian dan Pengembangan Daerah Kota Surakarta, 2024)
The increase in waste correlates with changes in consumption habits and population expansion. The Circular Economy, a primary focus in addressing climate change, promotes recycling and material integration in production. Industry 4.0 plays a crucial role with technologies like IoT, big data, and AI, enhancing raw material efficiency and waste reduction. SMEs in Surakarta have significant potential in transitioning towards a sustainable economy, leveraging their creativity to innovate in sustainable practices. This study aims to analyze the capabilities of SMEs in Surakarta in circular economy practices towards achieving a sustainable-smart city. Employing a quantitative approach, the study surveyed 215 research respondents using convenience sampling. Data analyzed through Partial Least Square-Structural Equation Modeling (PLS-SEM) highlights the pivotal role of Industry 4.0 readiness in adopting IIoT and big data analysis, driving circular economy practices. Managerial recommendations for SMEs include enhancing technological readiness and adopting the "reduce, reuse, recycle" approach. Government prioritization of training, digital infrastructure, and collaboration is crucial in supporting SMEs.